2018
DOI: 10.1111/jcpt.12718
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of home delivery programme in haemophilia

Abstract: The home delivery programme guarantees a proper follow-up of treatments with full patient satisfaction. This programme allows OPCU to achieve better pharmaceutical care, traceability of the process and optimization of working times and CF stock management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…24 Adherence and TS could be further improved by home-delivery programmes guaranteeing a proper followup of treatments as demonstrated in a study in Spain where patients reported benefits of such a program due to less frequent visits to hospital and reduced time and cost spent on transportation. 42 Adult patient's HRQoL improved from baseline to followup in the total score and the domains 'work' and 'dealing'. This fact might be related to the implementation of the MHOC concept provided to patients with an extra support in social-and work-related issues allowing them to deal better with the circumstances and social consequences of their disease.…”
Section: Discussionmentioning
confidence: 94%
“…24 Adherence and TS could be further improved by home-delivery programmes guaranteeing a proper followup of treatments as demonstrated in a study in Spain where patients reported benefits of such a program due to less frequent visits to hospital and reduced time and cost spent on transportation. 42 Adult patient's HRQoL improved from baseline to followup in the total score and the domains 'work' and 'dealing'. This fact might be related to the implementation of the MHOC concept provided to patients with an extra support in social-and work-related issues allowing them to deal better with the circumstances and social consequences of their disease.…”
Section: Discussionmentioning
confidence: 94%
“…Sixteen studies (51.6%) rated patients' levels of satisfaction with the interventions. 8,21,25,26,28,32,34,38,43,58,62,68,72,74,78,86 In general, these studies used an ad hoc approach to measure satisfaction. Only Van den Bosch et al, 62 applied the Treatment Satisfaction Questionnaire for Medication (TSQM) to assess patient satisfaction.…”
Section: Effect Of Home Care Services or Home Delivery Systems On Adherence To Medication Humanistic (Patient-reported Outcomes) And Econmentioning
confidence: 99%
“…Most of the services assessed involved nurse-led programs (n = 11; 68.8%), 8,21,25,26,28,32,34,38,43,58,62,72 and home medication delivery (n = 5; 31.2%). 25,26,28,62,74,86 Patients with various pathologies expressed their satisfaction with the interventions. Specifically, patients with multiple sclerosis indicated a very high level of satisfaction with home treatment, 8,21 and 98% decided to receive future infusions at home.…”
Section: Effect Of Home Care Services or Home Delivery Systems On Adherence To Medication Humanistic (Patient-reported Outcomes) And Econmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, it could lead to erroneous decisions, such as inappropriately modifying hemostatic treatment or misinterpreting the interactions that the latter might cause in coagulation tests, which could lead to incorrect assessment of the hemorrhagic/thrombotic risk of patients with congenital blood diseases and COVID -19. No different criteria should be established regarding the admission, hospitalization, or intensive care unit admission of patients with hemophilia with respect to the rest of the population, just as there are no contraindications for the use of drugs that are currently being used for COVID-19 treatment [22][23][24][25].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%